2010
DOI: 10.3986/ac.v39i3.83
|View full text |Cite
|
Sign up to set email alerts
|

Speleothems and speleogenesis of the hypogenic Santa Barbara Cave System (South-West Sardinia, Italy)

Abstract: This paper presents t�e results of a study on t�e speleogenesis and t�e speleot�ems and secondary mineralisations of t�e Santa Barbara Cave System in t�e Iglesiente Mining District (Sout�-West Sardinia, Cagliari). This cave system, �osted in Cambrian carbonate rocks, �as a very long geological �istory and its main voids �ave formed in �ypogenic conditions. Nine speleogenetic p�ases can be recognised ranging in age between Cambrian and Holocene. Optical microscope and diffractometric analysis of active flowston… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…Calcitization has been recognised in a certain number of caves (Folk & Assereto, 1976;Cabrol & Coudray, 1982;Frisia et al, 2002;Woo & Choi, 2006;Pagliara et al, 2010). This process takes place by dissolution at the microscale of metastable aragonite and precipitation of the stable phase, calcite (Perdikouri et al, 2008), when waters are undersaturated in aragonite and oversaturated in calcite (Maliva et al, 2000;Frisia et al, 2002).…”
Section: Calcitizationmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcitization has been recognised in a certain number of caves (Folk & Assereto, 1976;Cabrol & Coudray, 1982;Frisia et al, 2002;Woo & Choi, 2006;Pagliara et al, 2010). This process takes place by dissolution at the microscale of metastable aragonite and precipitation of the stable phase, calcite (Perdikouri et al, 2008), when waters are undersaturated in aragonite and oversaturated in calcite (Maliva et al, 2000;Frisia et al, 2002).…”
Section: Calcitizationmentioning
confidence: 99%
“…Relatively Mg enriched waters, as those found in Castañar Cave, can explain the formation of this type of calcite, and they would also be responsible for the presence of aragonite in the studied drapery, since it is commonly accepted that aragonite forms in the speleothems when Mg/Ca ratios in the waters are high (Cabrol & Coudray, 1982;González & Lohmann, 1988;Frisia et al, 2002;Rowling, 2004) due to the inhibiting role of Mg 2+ in calcite growth (Berner, 1975;Lippmann, 1973;Fernández-Díaz et al, 1996). Commonly, the high Mg/Ca necessary for aragonite formation has been related to evaporation that may accompany seasonal dryness (Railsback et al, 1994) and warmer and dryer climatic conditions (Pagliara et al, 2010), although aragonite precipitation has also been reported in comparatively wet climatic conditions due to the effect of Zn 2+ or Pb 2+ in inhibiting precipitation of calcite (Caddeo et al, 2011). of the primary texture.…”
Section: Controls On Primary Mineralogy Of Speleothemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its development must thus be placed below the water table, at least predominantly, as demonstrated by the presence of barite crystals and calcite cave clouds. During approximately the past one million years meteoric drip water has deposited large vadose calcite and aragonite speleothems making this chamber one of the most extraordinary cave environments of the world, of great scientific importance (Forti et al ., ; Pagliara et al ., ). These chemical deposits also sealed up part of the cave passages, allowing for the formation of a perched lake in the lowest part of Santa Barbara 1 cave.…”
Section: Hypogean Karst Formsmentioning
confidence: 99%